SUPPORTING STUDENT WELL-BEING: INTEGRATING COUNSELLING PSYCHOLOGY INTO OPEN AND DISTANCE EDUCATION - Daodu, Morufu Adedayo; Elegbede, Christie Bola; Abidogun, Moruf Adebayo (Faculty of Administrative Science, Universitas Brawijaya, 2023)
In the ever-evolving landscape of higher education, open and distance education has become a prominent mode of learning, facilitated by advances in technology and increased accessibility. While it offers unprecedented opportunities for remote learning, it also presents unique challenges, particularly in terms of student well-being. This study delves into the critical role of integrating counselling psychology services into open and distance education to enhance student well-being and promote academic success. This study is to explore how the integration of counselling psychology can effectively address the challenges faced by students in remote learning environments. These challenges include social isolation, heightened stress levels, motivation issues, and the absence of face-to-face interaction with instructors and peers. A mixed-methods research design was adopted, data collection used include survey and interview. Purposive sampling was employed to select participants who were actively engaged in open and distance education programs; descriptive and inferential statistics were used for data analysis. The results of this investigation reveal compelling evidence regarding the positive correlation between counselling psychology support and student well-being in open and distance education. The findings emphasising the potential implications for educational institutions and policymakers. It explores the ways in which counselling psychology can be effectively integrated into open and distance education, ensuring students receive emotional support, academic guidance, and timely crisis intervention when needed. This study underscores the significance of integrating counselling psychology services into open and distance education. By doing so, educational institutions can create a more supportive and conducive learning environment, ultimately enhancing student well-being and academic success. This research provides valuable insights and recommendations for educators, administrators, and policymakers aiming to improve the quality of remote learning experiences.